Corporate Strategy Configuration, Financial Performance, and Real Estate Asset Quality as Determinants of Market Valuation: Evidence from Indonesian Listed Property Developers - Saza Taupiq Ahmad; Raden Aswin Rahadi (Indonesian Journal Publisher, 2026)
Indonesian listed property developers with significant presence in Greater Jakarta have experienced a persistent decline in market valuation between 2015 and 2025, a pattern that predates and outlasted the Covid-19 shock and cannot be attributed to weak physical property demand, which remained resilient throughout the period. This study investigates the determinants of this valuation gap through an integrated framework combining Corporate Strategy Configuration, Financial Performance, and Real Estate Asset Quality as direct and moderating predictors of market valuation, alongside macroeconomic and firm-specific conditions (Bank Indonesia interest rate, inflation, the Covid-19 period, company size, and divestment activity). Using an eleven-year panel of 13 purposively sampled listed property developers with a one-year lagged structure, the study applies Partial Least Squares Structural Equation Modelling (SEM-PLS) together with Multi-Group Analysis (MGA) across firm-size and revenue-model subgroups, triangulated with three expert interviews. The model explains a substantial share of variance in valuation (R² = 0.566, adjusted R² = 0.533). Corporate Strategy Configuration, Company Size, Divestment Activity, Inflation, and Covid-19 emerge as significant direct predictors, while Financial Performance, Real Estate Asset Quality, and the BI Rate do not. Both moderation paths are non-significant, indicating that Asset Quality functions as an independent valuation signal rather than a conditioning mechanism. MGA results show that valuation dynamics differ significantly by revenue-model orientation, with the model explaining valuation considerably better for sales-oriented developers than for recurring-income developers, and more narrowly by firm size, where Asset Quality and Inflation are priced differently across large and medium developers. The findings indicate that the Indonesian property-developer valuation discount is driven principally by scale, strategic financing posture, and revenue-model orientation rather than by asset accumulation or macroeconomic conditions alone, offering an evaluative framework for investors, actionable guidance for management, and evidence that capital-market interventions targeted at medium-sized, sales-oriented developers may be more effective than broad monetary measures in supporting Indonesia's housing agenda